Achieving Educational Equity in Luwu Regency: An Evaluation of the Indonesia Pintar Program Policy - Anto, Anto; Mappasere, Fatmawati A.; Mustari, Nuryanti (Universitas 17 Agustus 1945 Surabaya, 2024)
The poverty rate in the Luwu district is relatively low, but the dropout rate in the region is still high. This is partly due to the high cost of education. In this area, the government initiated the Smart Indonesia Program and the Smart Indonesia Card (KIP) to provide educational cash assistance to all students meeting the specified requirements. This study aims to evaluate the implementation of the Smart Indonesia Program (PIP) at SDN 494 Pongko, Luwu Regency, focusing on educational equity, readiness, implementation, and utilization of the program. The research method is descriptive and qualitative, with data collection through in-depth interviews, observation, and documentation studies. The results show that the implementation of PIP at SDN 494 Pongko has been run by the established policy objectives and provided tangible benefits for parents and students receiving assistance. However, efficiency issues such as delays in fund disbursement need to be improved. There are inequalities in the distribution of aid caused by incomplete documentation. In conclusion, although the Smart Indonesia Program has contributed positively to increasing student participation and reducing the economic burden on parents, there is still a need for continuous evaluation and improvement to ensure better educational equity in Luwu District.